An annotated catalogue of the Coleoptera types deposited in the National Insect Collection (CNIN) of the National Autonomous University of Mexico - Zaragoza-Caballero, Santiago; Pérez-Hernández, Cisteil Xinum (Zootaxa, 2017)
The National Insect Collection (CNIN) constitutes the most representative entomological collection in Mexico. The coleopterans housed in the collection, mainly sampled in national territory, are represented by approximately 350,000 adult specimens mounted on entomological pins and nearly 250,000 preserved in alcohol. This catalogue includes information regarding 765 species from 255 genera classified into 34 families of Coleoptera types: Belidae Schönherr, Brentidae Billberg, Buprestidae Leach, Cantharidae Imhoff, Carabidae Latreille, Cerambycidae Latreille, Chrysomelidae Latreille, Cleridae Latreille, Curculionidae Latreille, Dytiscidae Leach, Elateridae Leach, Elmidae Curtis, Endomychidae Leach, Erotylidae Latreille, Geotrupidae Latreille, Heteroceridae MacLeay, Hydraenidae Mulsant, Hydrophilidae Latreille, Lampyridae Rafinesque, Leiodidae Fleming, Limnichidae Erichson, Lycidae Laporte, Meloidae Gyllenhal, Melolonthidae MacLeay, Passalidae Leach, Phengodidae LeConte, Ripiphoridae Gemminger, Scarabaeidae Latreille, Silphidae Latreille, Silvanidae Kirby, Staphylinidae Latreille, Telegeusidae Leng, Tenebrionidae Latreille and Zopheridae Solier. The total of 3,487 type specimens encompasses 468 holotypes, 100 allotypes, 2,911 paratypes, one neotype and four syntypes.